The microeconomics of income distribution dynamics in East Asia and Latin America - Bourguignon, François.; Ferreira, Francisco H.G.; Lustig, Nora Lustig (Washington, DC : World Bank ; [New York] : Oxford University Press, 2004)
This book presents a fascinating collection of studies on the dynamics of income inequality based on micro data.
"A copublication of the World Bank and Oxford University Press."
Includes bibliographical references and index.
aug 30/04/13; oif 04/05/15
Loans
Keywords: Income distribution -- Southeast Asia